Benzobisthiadiazole-alt-bithiazole copolymers with deep HOMO levels for good-performance field-effect transistors with air stability and a high on/off ratio. Issue 16 (23rd March 2016) - Zhang, Chen; Zhang, Ji; Zeng, Weixuan; Zheng, Naihang; Li, Wei; Gao, Wei; Yu, Gui; Yang, Chuluo
Abstract : Two benzobisthiadiazole- alt -bithiazole copolymers were designed and synthesized, and the resulting transistors achieved high performance with air stability and a high on/off ratio. Abstract : Benzobisthiadiazole (BBT ) is a widely used building block for its high electron affinity and planar configuration.BBT -based copolymers have resulted in good performance of organic field-effect transistors (OFETs). However, devices of these polymers are usually unstable in ambient air since most of theseBBT -based polymers have high-lying HOMO energy levels (−4.3 to −4.8 eV). Besides, the field-effect transistors (FET) ofBBT -based polymers show relatively low on/off ratios (10 2 –10 4 ). As a result, it is very attractive to couple BBT with an electron-deficient block to construct new polymers with air stability. 2, 2′-Bithiazole (BTz ) is a potential building block due to its electron deficiency and trans -planar configuration. But incorporating 2, 2′-bithiazole into polymers still remains a challenge since the organic tin compound of bithiazole is difficult to synthesize. In this article, we successfully prepared 5, 5′-bis(trimethylstannyl)-2, 2′-bithiazole by a three-step method and then synthesized two benzobisthiadiazole- alt -bithiazole copolymers (P1 andP2 ). BothP1 andP2 have a low-lying HOMO energy level (−5.3 eV), leading to air stability. Moreover the resulting FETs exhibit a very high on/off ratio (10 5 –10 7 ) and a good hole mobility of up to 0.11 cm 2 V −1 s −1, which represents a significant advancement forBBT -containing polymers.